Novo regime automotivo brasileiro: desafios e oportunidades da região sul fluminense - Pascoal, Erik Telles [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The public policies of incentives to the national automotive industries have been present since the implementation of this sector in Brazil. As example, in 2012, the federal government created a new Brazilian automotive policy, called Inovar-Auto, from 2013 to 2017, with the purpose of increasing the technological level associated to the products and process of automotive industry and the competitiveness of the sector. The present research aims to analyze and to evaluate the Inovar-Auto development in the automotive center of southern state of Rio de Janeiro, justified in the opportunity of exploit the new encouragement to the R&D and innovation activities for automotive sector, in the growing importance of the study area on the national scene and in a perspective to analysis an industrial public policy program even during its term. A field research was accomplished with companies of the studied region, through an elaborated questionnaire from Inovar-Auto's requirements and applied with directors and managers of these organizations. The results of this research revealed challenges related to the lack of knowledge and the understanding of the program's rules and also, development opportunities from partnerships between suppliers and automakers in R&D and innovations projects. Based on that, it was organized two regional forums of debate, with the purpose to promote a wide explanation of the program, sharing experiences among companies in the southern state of Rio de Janeiro in the conduct of Inovar-Auto's activities and to encourage the partnerships of these companies in R&D and innovation projects

As políticas públicas de incentivos à indústria automotiva nacional estão presentes desde a implantação deste setor no País. Como exemplo, em 2012, o governo federal criou o novo regime automotivo brasileiro, denominado Inovar-Auto, com vigência para o período de 2013 a 2017, com o intuito de elevar o nível tecnológico associado aos produtos e processos da indústria automotiva e aumentar a competitividade do setor. A presente pesquisa objetiva analisar e avaliar a evolução do Inovar-Auto no polo automotivo sul fluminense, justificada na oportunidade de explorar o inédito incentivo às atividades de P,D&I para o setor automotivo, na crescente importância da região de estudo no cenário nacional e na perspectiva de analisar um programa de política pública industrial ainda durante a sua vigência. Uma pesquisa de campo foi realizada junto às empresas da região estudada, por meio de um questionário elaborado a partir dos requisitos do Inovar-Auto e aplicado junto aos diretores e gerentes dessas organizações. Os resultados desta pesquisa revelaram desafios referentes à falta de conhecimento e de entendimento das regras do programa e, também, oportunidades no desenvolvimento de parcerias entre fornecedores e montadoras em projetos de P,D&I. Com base nisso, foram organizados dois fóruns regionais de debates, nos quais buscou-se promover um amplo esclarecimento do programa, compartilhar as experiências entre as empresas do sul fluminense na condução das atividades do Inovar-Auto e incentivar as parcerias destas empresas em projetos de P,D&I
New brazilian automotive policy: opportunities and challenges of region south of state of Rio de Janeiro
Keywords: Politicas publicas; Indústria automobilística; Inovações tecnologicas; Indústria automobilística - Nacionalização; Inovações tecnológicas - Países em desenvolvimento; Política tributária; Public policy